Konsep Dasar Manajemen Keuangan Dan Pembiayaan Pendidikan Dalam Pengelolaan Serta Pengalokasian Dana Pendidikan - MASRIANDA MASRIANDA (Jurnal Administrasi Pendidikan, 2022)
This study aims to determine the basic concepts of financial management and education financing in the management and allocation of education funds. This research is quantitative research with a correlational design. This study resulted indicate that educational financing management is all activities related to structuring the sources, use, and accountability of education funds in schools or educational institutions. Education is an important factor to realize quality human resources (HR), in fact, not everyone can get a proper education because of the high costs that must be incurred. This condition then prompted the inclusion of rules on education in the amendments to the 1945 Constitution. The constitution mandates the government's obligation to allocate 20% of education costs from the APBN and APBD so that the community can enjoy educational services, especially basic education. With the existence of 20% of the funding allocation from the APBN and APBD, it should be able to be used effectively and efficiently, besides that the education budget can be obtained from various sources, therefore management needs to be done.